Plugin CSS 100 POWER SOLUTIONS - Nixon, Robin (McGrawHill, 2012)
Plug-in CSS is filled with with ready-to-use CSS and HTML solutions for creating dynamic websites. Save hundreds of hours of programming time! Make your website look great with custom fonts, animated menu systems, individually styled forms, and other effects. This practical guide shows you how to do all of these things and much more using simple style sheet plug-ins.